Cluster Approach for Development of Tourism Infrastructure Based on the Supply Chain Management in the Region - Liliya Raisovna Fakhrutdinova; Gulnara Raisovna Chumarina; Boris Mojshevich Eidelman; Oleg Aleksandrovich Bunakov (International Journal of Supply Chain Management, 2019)
In article authors describe value of tourism infrastructure in the region. Tourism infrastructure is a complex system which consists of a set of elements of various branch accessory. Uniform development of each element is possible only thanks to the supply chain management. Owing to the complexity, tourism infrastructure and its components are an object of regional government. The instrument of development of tourist infrastructure is adoption of various programs of development of tourism in regions. Authors believe that a perspective way of development of tourism infrastructure of the region and in general the tourist industry is creation of a tourist cluster. The tourist cluster represents the merging of the enterprises of various sectors serving clients concentrated in a certain territory, and also investments and innovations. Hotels, food objects, tourist operators and tourist agents, transport enterprises, entertainment complexes can treat such enterprises. The purpose of creation of tourist clusters is improving competitiveness and formation of image of the region in the tourist market thanks to effective work of the organizations and enterprises entering a cluster. The main essence of a cluster – an opportunity for business and for the region to develop not by inertia. Tourist clusters are formed on the basis of operation of the mechanism of public-private partnership and scientifically based decisions that allows to create the best conditions for development of tourism infrastructure and related services. Along with development of tourism infrastructure, cluster approach allows to stir up activity of the regional enterprises of the different branches of economy for satisfaction of the growing needs for high-quality tourist services at increase in regional tourist streams.